Performance of Downlink NOMA Network Using Space-Time Line Coding Technique - Yilmaz, Tayfun; Ayranci, Ahmet Aytug; Ilhan, Haci (IEEE, 2021)
In this study, the bit error performance of a downlink Non-Orthogonal Multiple Access (D-NOMA) based network using Space-Time Line Coding (STLC) technique in the transmitter for communication with three users was investigated. Therefore, the STLC structure proposed in the literature has been adapted to the D-NOMA network and bit error performances of each user in the network have been examined through Monte-Carlo simulations. It has been considered that the base station is equipped with a single antenna and each mobile user equipped with two antennas in the network. Also, it is assumed that the fading channels between the users and the base station are independent and identically distributed (i.i.d.) and follow the Rayleigh distribution. Besides, it has been assumed that there was no error propagation in the Successive Interference Cancellation process (Perfect SIC), and the effects of practical impairments such as channel estimation error (CEE), feedback delay (FBD) have been ignored.
Keywords: D-NOMA; STLC; Bit Error Performance; NONORTHOGONAL MULTIPLE-ACCESS; Engineering; Telecommunications